What is strategic planning ? - Grinsted, Katherine; Ellis, Andrew ([S.l.] : Video Communicators [production company] ; Kuala Lumpur : First Training (M) [distributor])
Focused on the definition, method and the strategy of doing strategic planning.
Writer, Wilson Main, Stephen Taplin, Andrew Ellis
Keywords: Strategic planning